The Influence Of Company Reputation, Digital Marketing And Price Perception On Purchasing Decisions In The Shopee Marketplace - Galuh Roslan Nugraha; Adi Mulya Abdilah; Lis Tatin Hernidatiatin; Agustina Agustina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Unhealthy price competition in the market, especially due to predatory pricing practices, is a challenge for small and medium enterprises (SMEs). This study aims to analyze the influence of company reputation, digital marketing, and price perception on purchasing decisions in the Shopee marketplace. A quantitative approach was used with a survey method involving 200 respondents from the Cirebon area. After screening, the final sample size analyzed was 180 respondents. Data were collected through a questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with the help of SPSS 25.0. The results showed that price perception had a significant influence on purchasing decisions (p < 0.05), indicating that consumers tend to consider price when transacting on Shopee. Company reputation approached significance, while digital marketing did not show a significant influence, although it still played a role in attracting consumer attention. The regression model used proved strong (F = 27.840, p < 0.000), indicating that the independent variables collectively influenced purchasing decisions. In conclusion, the most dominant factor influencing purchasing decisions on Shopee is price perception. Although company reputation and digital marketing did not show strong individual significance, both still contribute collectively. Therefore, improving price transparency, maintaining positive company image, and enhancing digital marketing strategies are essential to increase consumer purchasing decisions in online marketplaces like Shopee.